Demonstration of Coinfection with and Recombination by Caprine Arthritis-Encephalitis Virus and Maedi-Visna Virus in Naturally Infected Goats - Pisoni, Giuliano (American Society for Microbiology, 2007)
Recombination of different strains and subtypes is a hallmark of lentivirus infections, particularly for human immunodeficiency virus, and contributes significantly to viral diversity and evolution both within individual hosts and within populations. Recombinant viruses are generated in individuals coinfected or superinfected with more than one lentiviral strain or subtype. This, however, has never been described in vivo for the prototype lentivirus maedi-visna virus of sheep and its closely related caprine counterpart, the caprine arthritis-encephalitis virus. Cross-species infections occur in animals living under natural conditions, which suggests that dual infections with small-ruminant lentiviruses (SRLVs) are possible. In this paper we describe the first documented case of coinfection and viral recombination in two naturally infected goats. DNA fragments encompassing a variable region of the envelope glycoprotein were obtained from these two animals by end-limiting dilution PCR of peripheral blood mononuclear cells or infected cocultures. Genetic analyses, including nucleotide sequencing and heteroduplex mobility assays, showed that these goats harbored two distinct populations of SRLVs. Phylogenetic analysis permitted us to assign these sequences to the maedi-visna virus group (SRLV group A) or the caprine arthritis-encephalitis virus group (SRLV group B). SimPlot analysis showed clear evidence of A/B recombination within the env gene segment of a virus detected in one of the two goats. This case provides conclusive evidence that coinfection by different strains of SRLVs of groups A and B can indeed occur and that these viruses actually recombine in vivo.